Can Mean Platelet Volume be Used as a Marker in Children with Acute Appendicitis? - Gülay Çiler Erdağ; Fatma Tuba Coşkun; Suat Biçer; Meltem Uğraş; Tuba Giray; Çiğdem Kaspar; Öznur Küçük; Defne Çöl (Journal of Pediatric Emergency and Intensive Care Medicine, 2017)
Introduction: The primary aim of this study was to investigate the diagnostic value of mean platelet volume (MPV) in the diagnosis of acute appendicitis and the effect of the presence of complication on MPV values in children with acute appendicitis. Methods: Mean MPV values were retrospectively compared between children who were diagnosed with acute appendicitis by clinical and pathological methods and healthy children (n=51). Children with peritonitis, necrosis, perforation and/or abscess were classified as complicated appendicitis. Mean MPV values were compared between children with and without complicated appendicitis. Statistical analyses were performed by student’s t-test, the Kruskal-Wallis, and Mann-Whitney U tests. Results: The mean age of the children (n=43, 68% was male) was 8.7±4.0 years (range: 1-17). The children were divided into 3 age subgroups: ≤3 years (n=7), 4-9 years (n=13), and 10-16 years (n=23). Complicated appendicitis was detected in 71.4%, 30%, and 21% of children in ≤3 years, 4-9 years, and 10-17 years subgroups, respectively. Complicated and noncomplicated appendicitis was detected in 12 (28%) and 31 (72%) children, respectively. Mean MPV values were not significantly different between children with (9.4±0.5 fL) and without (9.3±0.6 fL) acute appendicitis (p>0.05). Mean MPV values were not significantly different between complicated (9.5±0,5 fL) and noncomplicated (9.4±0.4 fL) groups (p>0.05). Conclusion: It was observed that MPV is not a suitable marker for acute appendicitis in children in the first nine years of life. Additionally, MPV is not useful to discriminate between complicated and noncomplicated appendicitis in children aged between 1 and 17 years.